Polyhydroxyalkanoate production from unexplored sugar substrates (2014)
Industrial-scale production of biopolymers is restricted by its elevated production costs in comparison with those associated with synthetic (no-biodegradable and no-biocompatible) polymers. In this study we tested for the first time two low-cost carbon substrates (i.e. carob pulp and fique juice) for lab-scale production of polyhydroxyalkanoate (PHA) with Bacillus megaterium. PHA detection and quantification was conducted by gas chromatography/mass spectrometry-selected ion monitoring (GC/MS-SIM). The results suggest that PHA production using carob pulp (from Hymenaea courbaril) may be as high as with sugar cane molasses. Moreover, it could serve for the synthesis of the most commercialized type of PHA (i.e. polyhydroxybutyrate; PHB) and/or other varieties (e.g. polyhydroxy-butyrate-co-valerate; PHBV) with different properties and potential applications.